2017
DOI: 10.30998/deiksis.v9i03.848
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Teknologi Pembelajaran Blended Learning terhadap Hasil Belajar Menulis Teks Fungsional Pendek Bahasa Inngris

Abstract: <p>Tujuan dari penelitian ini adalah untuk mengidentifikasi masalah dan kesulitan apa saja yang di alami oleh para siswa ketika mereka belajar menulis teks fungsional pendek bahasa Inggris, mengetahui apakah teknologi pembelajaran Blended Learning mempengaruhi hasil belajar menulis teks fungsional pendek bahasa inggris dan mengetahui apakah terdapat pengaruh penggunaan teknologi pembelajaran blended learning terhadap hasil belajar menulis teks fungsional pendek bahasa Inggris pada siswa kelas VII SMPN 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…These findings supported the research conducted by Koud (2007) who proved the effectiveness of internet blended discussion group on developing composition writing skills of first year of secondary school students. In addition, the finding of this study also supports Permana (2017) and Muthoharoh (2017) in the sense that the use of blended learning could similarly have significant effect on students' writing competency.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings supported the research conducted by Koud (2007) who proved the effectiveness of internet blended discussion group on developing composition writing skills of first year of secondary school students. In addition, the finding of this study also supports Permana (2017) and Muthoharoh (2017) in the sense that the use of blended learning could similarly have significant effect on students' writing competency.…”
Section: Discussionsupporting
confidence: 73%
“…The result shows that there is a significant effect of using blended learning strategy toward the students' writing competency. Another study was also conducted by Muthoharoh (2017) which focused on the effect of blended learning technology toward learning outcomes of English short functional text at SMP Negeri 98 Jakarta Selatan using Edmodo platform of e-learning.The result shows that there is a significant influence of using blended learning technology towards learning outcomes of English short functional text in the seventh grade students of SMP Negeri 98 Jakarta Selatan.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that the application of blended learning was able to positively influence learning outcomes (Muthoharoh, 2017). In addition, Usman (2018) found that the blended learning method was able to improve the quality and quality of learning and was able to increase the motivation, interest and learning outcomes of students.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research found that the application of blended learning was able to positively influence learning outcomes [12]. In addition, Usman [13] found that the blended learning method was able to improve the quality and quality of learning and was able to increase the motivation, interest and learning outcomes of students.…”
Section: Introductionmentioning
confidence: 99%